G83(P) Fish-oil based intravenous lipid emulsion as a rescue in septic infants with intestinal failure and with or at risk of developing liver disease. (7th April 2014) - Lee, HM; Hickey, A; Callaby, H; O'Meara, M; Thompson, L; Hind, J
Abstract : Aims: In infants with intestinal failure, it is known that episodes of sepsis can be accompanied by a significant deterioration in liver function. We hypothesised that an intravenous lipid emulsion (ILE) comprised solely of fish oil, such as Omegaven ®, may protect the liver in these infants during episodes of sepsis. Our aim is to describe our single centre experience with Omegaven ® as a rescue therapy in septic infants with intestinal failure and with or at risk of developing liver disease. Methods: A mixed source ILE containing both omega-3 and omega-6 fatty acids (SMOFlipid ® ) was used as first-line in infants at high risk of intestinal failure-associated liver disease (IFALD) or severe liver disease. When these infants developed sepsis, Omegaven ® was used as the sole ILE for up to 14 days. A retrospective review of their case notes was conducted. Results: 10 infants had Omegaven ® treatment during a 2-year period (August 2011–August 2013). Of the 10 patients, 2 had gastroschisis, 5 had necrotising enterocolitis (NEC), 2 patients had congenital infection with conjugated hyperbilirubinaemia, and 1 had conjugated jaundice associated with maternal liver failure. Median age at start of Omegaven ® was 38 days (range 2–189). 1 patient had 3 courses of Omegaven ® treatment due to recurrent episodes of sepsis. 9 patients had conjugated hyperbilirubinaemia with total bilirubin levels above 80 μmol/l at commencement of Omegaven ® . Out of these 9 patients, 5 had conjugated bilirubin levels above 100 μmol/l when Omegaven ® was started. During their episodes of sepsis, bilirubin and CRP rose as expected in all patients. Transaminases were deranged in all. Those with established liver disease did not demonstrate the marked rise in bilirubin that would normally be anticipated. In those that were treated prophylactically, the liver function did not show marked deterioration despite the severity of sepsis. 7 patients showed improvement in bilirubin levels during treatment and this was maintained in the long term in 6. Conclusion: Use of Omegaven ® as a short term rescue ILE in septic infants with intestinal failure and with or at risk of developing liver disease appears safe. The expected deterioration in liver function associated with sepsis was not seen in this series.